Refugee securitization and the challenges of formal integration: case of Somali refugees in Kenya and Ethiopia - Fred N. Ikanda; Abdirahman A. Muhumad; Jana Kuhnt (Comparative Migration Studies)
Abstract Securitization of refugees and migrants is a growing global phenomenon that is well illustrated by how refugee camps have emerged as governmental technologies of control in major host countries across the world. Policymakers and the media prominently feature the migration-security connection and depict refugees as threats to internal security, linking their presence to acts of terrorism and crime. This article examines how the securitization of Somali refugees in Kenya and Ethiopia, the two main host countries for this refugee group, has hindered their formal integration and exacerbated policies of encampment in these countries. Drawing on securitization theory, we highlight the discrimination of Somali refugees in Kenya and Ethiopia by demonstrating how this refugee group is seen as a specific security threat and treated differently from other refugee groups in these countries. A history of border conflicts that shaped the relationship between refugee hosting areas and the national governments long before the advent of camps, coupled with shared Somaliness between locals and refugees in hosting areas, and the back-and-forth refugee movements across international borders have created a confluence of factors that reinforce suspicion and distrust towards Somali refugees. The article adds a normative empirical dimension to securitization theory by providing a nuanced understanding of the concept as it applies to different refugee groups in similar contexts. It also contributes to refugee and migration literature by arguing that although shared Somaliness with locals has strengthened the informal integration of Somali refugees in the two study contexts, the same ties have also provided justification for securitizing this refugee group and denied it from benefitting from progressive laws on formal integration that are being implemented for other refugee groups.